2016
DOI: 10.3390/s16122038
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Implement IoT Network Performance Modelling Techniques for Network Solution Selection

Abstract: No single network solution for Internet of Things (IoT) networks can provide the required level of Quality of Service (QoS) for all applications in all environments. This leads to an increasing number of solutions created to fit particular scenarios. Given the increasing number and complexity of solutions available, it becomes difficult for an application developer to choose the solution which is best suited for an application. This article introduces a framework which autonomously chooses the best solution fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It becomes an issue to select most suitable solution for a given application. A framework has been proposed using which one can select most suitable IOT based solution for implementing an application in a specified environment [11]. The framework helps to assess the performance of a solution chosen to implement an application under a defined environment.…”
Section: Related Workmentioning
confidence: 99%
“…It becomes an issue to select most suitable solution for a given application. A framework has been proposed using which one can select most suitable IOT based solution for implementing an application in a specified environment [11]. The framework helps to assess the performance of a solution chosen to implement an application under a defined environment.…”
Section: Related Workmentioning
confidence: 99%
“…Effective evaluation of proposed models cannot be achieved without standard evaluation metrics (Delaney and O'Hare, 2016). This study's literature has demonstrated inconsistent performance metrics, especially in testbed deployment, where the models interact with real traffic with varying traffic intensities and different performance requirements.…”
Section: Resultsmentioning
confidence: 99%
“…In [17], the authors describe the experimental environment and methodologies to model the throughput of a transmission control protocol connection. The experimental results therein show that the throughput can be predicted with a very high accuracy using a support vector machine model [18]. In [19], the authors show that operators and service providers can adapt their services and contents using prediction models based on user's experience feedback.…”
Section: A Related Workmentioning
confidence: 98%